CONTINUOUS MIDWIFERY CARE FROM PREGNANCY TO FAMILY PLANNING AT WONOAYU PUBLIC HEALTH CENTER, SIDOARJO: CASE STUDY - Roida Ulyah; Yanik Purwati (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2026)
Objective: The maternal mortality rate (MMR) is a key indicator of maternal health service quality. In Sidoarjo Regency, the MMR increased from 48.3 per 100,000 live births in 2023 to 88.5 per 100,000 live births in 2024. Continuity of Care (COC) is one approach to reducing maternal and infant mortality. This study aims to describe the implementation of COC from pregnancy to family planning services and to evaluate its outcomes on maternal and neonatal conditions. Methods: This study used a qualitative descriptive case study design conducted at the Wonoayu Community Health Center, Sidoarjo. One pregnant woman receiving continuous midwifery care from the third trimester through postpartum family planning was selected as the subject. Data were collected through anamnesis, physical examination, observation, and care documentation, and analyzed descriptively by comparing case findings with midwifery service standards and relevant theories. Results: The study results showed that the implementation of continuous midwifery care was carried out in accordance with midwifery service standards. Throughout the care process, the condition of the mother and baby was within normal limits, with no complications observed during pregnancy, delivery, postpartum, or the neonatal period. Conclusion: Continuous midwifery care at Wonoayu Community Health Center has been implemented according to midwifery service standards and takes place physiologically. The implementation of this approach needs to be continuously maintained and developed by health workers, and further research is recommended to involve a larger number of respondents to strengthen scientific evidence regarding the effectiveness of continuity of care. Keywords: Continuity of Care, Pregnancy, Postpartum, Newborn, Family Planning